"Ao som do mar e à luz do céu": dinâmicas das imagens turísticas dos paraísos litorâneos no Brasil - Castro, Tiago da Silva (2021)
The constitution of sun and beach destinations in Brazil is beyond the planning applied in the 1990s, since certain coastal locations received the first flows of visitors in 1960, in an embryonic stage of what would become a model to be followed in the following decades. In this period, characterised by the circulation of curious and adventurous travellers, the main tourist facilities were the homes of families linked to subsistence activities. In the following years these villages became very important in the network of tourist areas in various scales, receiving flows of tourists and national and international investments. These are the cases of Jericoacoara/CE, Maragogi/AL, Morro de São Paulo/BA, Pontal do Atalaia/RJ and Bombinhas/SC. These resorts, with their images associated with religious and historical representations of divinely conceived spaces, represent what can be called tourist paradises. The aim here is to investigate the factors and dynamics that contribute to the growth and maintenance of tourist images and the process of touristification in the coastal paradises in Brazil. To this end, the bibliographical and documental survey enables analyses about the function of the concept of paradise for religion and tourism, about the beach valorization process, the touristification agents and the territorial planning in the different scales enabling the understanding of the similarities in the processes and specific issues of each selected case. Then it is necessary to understand, through the survey of travel magazines, digital content and metadata (folksonomy), the importance of the tourist as a constituent agent of the imaginary of the destinations. We conclude that the coastal paradises are constituted by very particular dynamization processes, initiated by centric travelers and motivated by associations with religious myths and, due to environmental, social, territorial and political particularities, are constituted as destinations of relevant tourist success and by distinct urban forms in relation to metropolitan destinations and coastal metropolises.